2018
DOI: 10.1016/j.imr.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of clinical factors that influence the use of traditional Korean medicine among children with cerebral palsy

Abstract: BackgroundTraditional Korean medicine (TKM) is widely used to treat children with cerebral palsy (CP) in Korea; however, studies investigating factors that influence the use of TKM are scarce. Thus, we investigated the clinical factors that might influence the use of TKM.MethodsA population-based, cross-sectional, multicenter survey was performed from August 2014 to May 2016. The history of TKM use, type and severity of CP, current treatment characteristics, presence of accompanying disabilities or other healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…19) We previously observed that children with non-spastic CP tended to use TKM more than those with spastic CP. 13) The present findings are consistent with these previous findings. This suggests that TKM is more accessible to patients with uncommon atonic, ataxic, or mixed CP than to those with spastic CP.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…19) We previously observed that children with non-spastic CP tended to use TKM more than those with spastic CP. 13) The present findings are consistent with these previous findings. This suggests that TKM is more accessible to patients with uncommon atonic, ataxic, or mixed CP than to those with spastic CP.…”
Section: Discussionsupporting
confidence: 94%
“…The added effect on combining TKM with conventional treatment should be investigated since the latter is currently administered as an adjuvant with conventional treatment. 13) This prospective, observational, and cross-sectional study examined factors affecting TKM use via survey administration following recruitment. 13) Patients with non-spastic-type CP or other health problems tended to be high-frequency users of TKM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with neuropsychiatric diseases use herbal medicine about 35.4% [24]. The elementary school-age children in South Korea have epileptic problems ~17.2% and they use herbal medicine at high range varying from 65.2% to 67.8% [25]. In Turkey, the prevalence of pediatric use of herbal drugs was 58.6% [26].…”
Section: Prevalence Of Herbal Medicinal Product Usementioning
confidence: 99%